Analysis of Sustainable Teacher Professionalism Development Post-Certification in SD Negeri Medang Kampai District, Dumai City - Juniar Juniar; Sumarno Sumarno; Sri Kartikowati (Journal of Educational Sciences, 2022)
This study aims to analyze (1) the reasons for the teachers of SD Negeri Medang Kampai in implementing PKB, (2) the efforts of teachers in implementing PKB, (3) the supporting and inhibiting factors in the implementation of PKB, (4) the efforts of the teachers of SD Negeri Medang Kampai in implementing PKB. The research data sources were five principals and forty-seven elementary school teachers in Medang Kampai District. The data collection technique used observation, interview and documentation techniques. The data analysis technique uses the Miles and Huberman model, namely data reduction, data display, and drawing conclusions. The results showed that (1) the reasons for teachers to follow PKB were to add insight, knowledge, creativity and improve professional competence, orders from school principals, and for promotion, (2) the efforts of teachers in implementing PKB were to follow seriously, 3) the supporting and inhibiting factors in the implementation (PKB) that come from the Office, the school and themselves, (4) the efforts of teachers in overcoming obstacles to the implementation (PKB) are involving teachers in PKB activities, providing as much related information as possible, motivating teachers to continue to be enthusiastic about participating in PKB activities.